Defining Shakespeare Pericles as test case - Jackson, MacDonald P. (MacDonald Pairman) (Oxford University Press, 2003)
'That very great play, Pericles', as T.S. Eliot called it, poses formidable problems of text and authorship. This book examines rival theories about the quarto's origins and offers evidence that 'Pericles' is the product of collaboration between Shakespeare and the minor dramatist George Wilkins.